Intravenous Application of Second-Generation Ultrasound Contrast Agents in Children: A Review of the Literature - Piskunowicz, M.; Kosiak, W.; Batko, T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
CEUS examinations using second-generation ultrasound contrast agents (UCA) are conducted in children, despite not being registered for individuals less than 18 years of age. We searched the Medline® database through Pubmed® and Scopus database, in order to find articles in which UCA were administered intravenously in patients under the age of 18. We analyzed in detail 9 papers (7 case reports, 2 original research studies), describing the examinations with intravenous administration of the UCA in children, and 23 original papers, in which the study group included at least one individual under the age of 18. Neither of the analyzed studies included any reports of adverse effects after UCA administration.
Keywords: ultrasound; contrast agents; children